Comparative Analysis of Cooling Load Calculations: CLTD Method vs. Carrier HAP 5.01 Software for Hotel HVAC Design - Madarif Prawibowo; Komarudin Komarudin (International Journal of Innovation in Mechanical Engineering and Advanced Materials, 2024)
This study examines the cooling load requirements of a hotel building by comparing two methodologies: the traditional Cooling Load Temperature Difference (CLTD) method and the Carrier Hourly Analysis Program (HAP) 5.01 software. The primary objective is to validate the accuracy and reliability of these methods in calculating cooling loads across different room types, from standard rooms to larger, more complex suites. The results show that the CLTD method consistently yields higher cooling load estimates, with discrepancies ranging from 3% to 14% compared to HAP 5.01 calculations. These differences are most significant in larger rooms, such as suites and owner’s suites, which have more extensive glass areas, higher occupancy, and more heat-generating equipment. The findings indicate that while the CLTD method is valuable for quick, preliminary estimates, the HAP 5.01 software provides a more precise and comprehensive analysis, taking into account hourly variations, equipment schedules, and other factors that impact cooling loads. This research highlights the need for careful selection of the appropriate calculation method to ensure the efficient design of HVAC systems, maximizing energy efficiency, and maintaining occupant comfort. The study concludes that for projects requiring high accuracy, particularly in complex or large spaces, dynamic simulation tools like HAP 5.01 are preferable. Detailed cooling load results and comparisons are provided in the supplementary documentation, offering further insights into the analysis and its implications for HVAC design.